2019
DOI: 10.1021/acs.analchem.9b03321
|View full text |Cite
|
Sign up to set email alerts
|

2D Graphene Oxide/Fe-MOF Nanozyme Nest with Superior Peroxidase-Like Activity and Its Application for Detection of Woodsmoke Exposure Biomarker

Abstract: Emerging nanomaterials such as nanozymes have recently been applied for the immunoassay-based detection of biomarkers. However, the inferior catalytic activity and low water solubility of nanozymes remain as the major limitations compared to natural enzymes. To overcome these limitations, we successfully synthesized a superior nanozyme with a structure of enriched 2D catalytic interface, namely Nanozyme Nest, which was composed of Fe-based metal–organic frameworks (Fe-MOF) and graphene oxide (GO). Then, we app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(59 citation statements)
references
References 58 publications
0
58
1
Order By: Relevance
“…42 For instance, Ruan et al reported the third generation of 2D GO/Fe-MOF hybrid nanozymes, named nanozyme nest, which was used in a conventional sandwich ELISA to detect benzo[a]pyrene-7,8-diol 9,10-epoxide−DNA adduct (BPDE−DNA), a woodsmoke biomarker found in the blood. 133 This method showed enhanced sensitivity for the oxidation of TMB by dual peroxidase active nanozyme nest(Fe-MOF and GO).…”
Section: Nanozyme As a Substitute Of Hrpmentioning
confidence: 99%
See 1 more Smart Citation
“…42 For instance, Ruan et al reported the third generation of 2D GO/Fe-MOF hybrid nanozymes, named nanozyme nest, which was used in a conventional sandwich ELISA to detect benzo[a]pyrene-7,8-diol 9,10-epoxide−DNA adduct (BPDE−DNA), a woodsmoke biomarker found in the blood. 133 This method showed enhanced sensitivity for the oxidation of TMB by dual peroxidase active nanozyme nest(Fe-MOF and GO).…”
Section: Nanozyme As a Substitute Of Hrpmentioning
confidence: 99%
“…Electrostatic interactions between GO and Fe-MOF hold them together. 133 A similar phenomenon was used for the synthesis of GO-AuNP nanozymes. During the aging step of the synthesis, gold ion was adsorbed on the surface of the GO.…”
Section: Synthesis Of Carbon-based Nanozymesmentioning
confidence: 99%
“…Nanozymes have recently shown great potentials in biomedical, [1–4] analytical, [5, 6] and environmental applications [7, 8] . Compared to their protein counterpart, nanozymes possess several unique advantages such as tolerance to harsh environment, resistance to protease digestion, and low cost [1, 9–11] .…”
Section: Figurementioning
confidence: 99%
“…[4,[19][20][21] While most peroxidase nanozymes work optimally at pH 4, their activity at neutralp Hi sn early fully inhibited. [9,22] Various methods were devoted to improve the catalytic activity of peroxidasenanozymes towards neutral pH, such as surfacemodification with metal ions, [6,13] polymers, [23] amino acids, [24] and small molecules. [25,26] For instance,a denosine triphosphate (ATP)-modifiedF e 3 O 4 nanoparticles showede nhanced activity at physiological pH.…”
mentioning
confidence: 99%
“…On the other hand, the peroxidase‐like activity of WS 2 has been used for colorimetric glutathione detection [13] . The enzymatic property of nGO has been evaluated for pesticide [14] and woodsmoke exposure biomarker [15] detection. Though their applications are highly appealing, the environmental factors diminishing or boosting the reaction rate have to be taken in account for the development of robust applied systems.…”
Section: Introductionmentioning
confidence: 99%